Relational Authenticity in Community: A Key for Support on the Spiritual Journey? - Oliva, Sarah (Ecclesial Futures, 2025)
As God leads his people in this current age, the church, ever-changing and growing, has responded with new expressions of independent community churches. Jesus’ mandate for the church to care for its people has not changed. How then, are independent community churches supporting the spiritual journeys of their congregants? This article presents a case study of The Big Table, an independent community church in South Perth, Western Australia. It uses interviews and participant observations to examine how spiritual support is provided beyond traditional church models. It draws from and extends, a theoretical framework of relational authenticity proposed by Lynne Taylor (2017), emphasizing its role in nurturing faith during seasons of doubt, crisis and transition. This has theoretical relevance as it extends Taylor’s research from recent converts to believers through faith transitions. The study shows how the deeply valued practices of community engagement, worship, Scripture exploration and relational leadership sustain spiritual formation and faith continuity, whilst highlighting the importance of relational authenticity as central to supporting believers across faith transitions. The article also has ministry relevance for understanding the journeys of believers who depart existing expressions of church, whilst retaining faith in God. It also holds practical relevance for church leaders exploring new expressions of church, offering insights into fostering meaningful spiritual engagement and support outside traditional frameworks.